Expression of polycystic ovary syndrome candidate genes in bovine fetal and adult ovarian somatic cells. Issue 4 (29th November 2022) - Liu, Menghe; Hummitzsch, Katja; Bastian, Nicole A; Hartanti, Monica D; Irving-Rodgers, Helen F; Anderson, Richard A; Rodgers, Raymond J
Abstract : Polycystic ovary syndrome (PCOS) is an endocrine metabolic disorder that appears to have a genetic predisposition and a fetal origin. The fetal ovary has two major somatic cell types shown previously to be of different cellular origins and different morphologies and to differentially express 15 genes. In this study, we isolated the somatic gonadal ridge epithelial-like (GREL) cells ( n   = 7) and ovarian fetal fibroblasts ( n   = 6) by clonal expansion. Using qRT-PCR, we compared the gene expression levels of PCOS candidate genes with previous data on the expression levels in whole fetal ovaries across gestation. We also compared these levels with those in bovine adult ovarian cells including fibroblasts ( n   = 4), granulosa cells ( n   = 5) and surface epithelial cells ( n   = 5). Adult cell types exhibited clear differences in the expression of most genes. In fetal ovarian cells, DENND1A and ERBB3 had significantly higher expression in GREL cells. HMGA2 and TGFB1I1 tended to have higher expression in fetal fibroblasts than GREL cells. The other 19 genes did not exhibit differences between GREL cells and fetal fibroblasts and FBN3, FSHB, LHCGR, FSHR and ZBTB16 were very lowly expressed in GREL cells and fibroblasts. The culture of fetal fibroblasts in EGF-containing medium resulted in lower expression of NEIL2 but higher expression of MAPRE1 compared to culture in the absence of EGF. Thus, the two fetal ovarian somatic cell types mostly lacked differential expression of PCOS candidate genes. Lay summary: Polycystic ovary syndrome (PCOS) is one of the most common reproductive problems. The cause is not known so there are no specific treatments or prevention strategies. We know it can be linked to issues that occur in the womb and that some people may be more likely to get PCOS due to their genetic makeup. Our recent studies showed that many of the genes linked to PCOS were found to be switched on in the fetal ovary and are likely to be involved in the development of the fetal ovary. In order to improve our understanding of PCOS, we need to identify the type of cells in the fetal ovary where these genes are switched on. In this study, we examined the PCOS genes in two types of cells that mature as the fetal ovary develops and found very little difference between them but bigger differences to their mature adult counterparts.